Perfectionism and attitudes towards doping in junior athletes - Madigan, D. J.; Stoeber, J.; Passfield, L. (Journal of Sports Sciences, 2016)
Recent theory and research suggest that perfectionism is a personal factor contributing to athletes` vulnerability to doping (using banned substances/drugs to enhance sporting performance). So far, however, no study has examined what aspects of perfectionism suggest a vulnerability in junior athletes. Employing a cross-sectional design, this study examined perfectionism and attitudes towards doping in 129 male junior athletes (mean age 17.3 years) differentiating four aspects of perfectionism: perfectionistic strivings, perfectionistic concerns, parental pressure to be perfect, and coach pressure to be perfect. In the bivariate correlations, only parental pressure showed a positive relationship with positive doping attitudes. In a multiple regression analysis controlling for the overlap between the four aspects, perfectionistic strivings additionally showed a negative relationship. Moreover, a structural equation model examining the relationships between all variables suggested that coach pressure had a negative indirect effect on attitudes towards doping via perfectionistic strivings. The findings indicate that perceived parental pressure to be perfect may be a factor contributing to junior athletes` vulnerability to doping, whereas perfectionistic strivings may be a protective factor.